Transforming growth factor beta-1 level in pleural effusion - KARAKURT, SAİT (BLACKWELL PUBLISHING ASIA, 2003)
Objective: Transforming growth factor-beta(1) is an important immunomodulator. The diagnostic role of TGF-beta(1) has not been systematically investigated in pleural effusion. Methodology: A prospective clinical study of 45 patients (23 men, 22 women; mean age 49 21 years) with pleural effusion was performed. Of these patients, 19 had malignant pleural effusion, 14 had tuberculous pleural effusion, seven had empyerna/parapneumonic pleural effusion, and five had transudative pleural effusion due to congestive heart failure. The concentrations of TGF-beta(1) were measured by ELISA in all pleural fluid samples and in serum samples only from patients with malignant and tuberculous pleural effusions. Results: The median TGF-beta(1) levels of malignant, tuberculous and empyema/parapneumonic pleural effusions were 7.25 ng/mL, 7.81 ng/mL, and 9.75 ng/mL, respectively. There was no significant difference between them. The median TGF-beta(1) level was 5.62 ng/mL in the transudate pleural effusion group and it was significantly lower than that in the empyema/parapneumonic group (P < 0.05). The pleural fluid TGF-beta(1) levels did not correlate with cell profiles of the pleural fluid. The median serum TGF-beta(1) levels in malignant and tuberculous pleural effusion groups were 7.38 ng/mL and 7.38 ng/ mL, respectively. There was no significant difference between the levels of TGF-beta(1) in paired samples of serum and pleural fluid. Conclusions: This study shows that TGF-beta(1) concentrations in exudative pleural effusions are higher than those in transudative effusions secondary to congestive heart failure but TGF-beta(1) concentrations do not assist in differentiating exudative effusions.
Keywords: cancer; infection; pleural effusion; transforming growth factor beta-1; tuberculosis; TGF-BETA; TUBERCULOSIS; DISEASE; CANCER; GROWTH-FACTOR-BETA-1; MESOTHELIOMA; EXPRESSION; CELLS